Technical report: comparing method in double pendulum / Siti Noor Aliah Nordin and Nor Amira Abdul Rahiim - Nordin, Siti Noor Aliah; Abdul Rahiim, Nor Amira (2016)
In this project paper, its present the motion of the curves in double pendulum by comparing the three types of method that related each other. Tue method that used in double pendulum are Lagrangian, Euler equation, Hamilton's and lastly Runge Kutta. This method are related each other because to derive the Euler equation, formula of Lagrangian is needed and also from Euler equation, it can derive into two types of method such as Hamilton's and Runge Kutta but Runge Kutta can also derive from Hamilton's. All this method are needed to know their motion, structure of wave, and so on. Mathematica software is needed for solving the problem of double pendulum and to get the accurate result based on graph of parametric and for animation, it is shows their movements. This software can solve all this method included Lagrangian.